18F-FDG PET/CT could Precisely Localize Hypermetabolic Cervical Muscles in a Patient Affected by Idiopathic Cervical Dystonia. Issue 1 (March 2013) - Paghera, Barbara; Caobelli, Federico; Motta, Federica; Giubbini, Raffaele
<x xml:space="preserve">Abstract</x> Background Idiopathic cervical dystonia [ICD] is characterized by an abnormal head and neck posture attributable to involuntary tonic or phasic contractions of neck muscles. Findings We performed a brain fluorine-18 fluorodeoxyglucose positron emission tomography/computerized tomography [F18-FDG PET/CT] scan for suspected metabolic alterations in basal ganglia in a 51-year-old woman without any evidence of secondary dystonia. Brain uptake was unremarkable, whereas an increased F18-FDG uptake was observed in the right trapezius and right longus colli muscle, allowing a diagnosis of ICD. Conclusion An F18 PET/CT may be a non-invasive alternative to electromyography to identify dystonic cervical muscles and this identification could lead to successful clinical results after targeted intramuscular botulinum toxin treatment.